2012
DOI: 10.1111/clr.12031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anodized titanium implants bioactivity

Abstract: Nanostructured surface titanium implants could be prepared by anodic oxidation with resultant accelerated bioactivity that may be recommended for early loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…This suggests that implant surface could be conditioned by different procedures. It is shown that both organic and inorganic impurities on the surface can increase WCA, so different decontamination technique were investigated [49]. On titanium surface exposed to UV-A treatment was observed a superhydrophilicity behavior, due to an increased anatase surface modifications [50].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that implant surface could be conditioned by different procedures. It is shown that both organic and inorganic impurities on the surface can increase WCA, so different decontamination technique were investigated [49]. On titanium surface exposed to UV-A treatment was observed a superhydrophilicity behavior, due to an increased anatase surface modifications [50].…”
Section: Discussionmentioning
confidence: 99%
“…Another common treatment for obtaining smooth sized features is acid‐etching (Herrero‐Climent et al, ; Medvedev et al, ; Saulacic, Erdosi, Bosshardt, Gruber, & Buser, ; Wennerberg, Svanborg, Berner, & Andersson, ). After performing dissolution of the original oxide layer, the selective dissolution of the substrate grains results in the acid etching process (El‐wassefy, Hammouda, Habib, El‐Awady, & Marzook, ). Natural passivation completes alongside exposing at ambient conditions to ensure the final surface roughness remains between 0.2 μm and 2 m (Zhao et al, ).…”
Section: Osteobiologic Materialsmentioning
confidence: 99%
“…The anodization processing of cpTi in the time range from 15 minutes to 120 minutes leads to the formation of a nanotubular oxide layer with limited thickness of about 2 μm after 120 minutes [14]. However, increasing anodizing time leads to decreasing the thickness of the nanotube wall [15].The nanotubular oxide layers formed on the titanium-based materials are compiled of the elements in the base material. For instance, nanotubular oxide layer formed on the Ti-Al alloy is composed of TiO2 and Al2O3.…”
Section: Fig 2 Formation Of the Oxide Layer On The Titanium Surfacementioning
confidence: 99%